2021
DOI: 10.9734/afsj/2021/v20i930342
|View full text |Cite
|
Sign up to set email alerts
|

Functional Properties of Complementary Food from Millet (Pennisetum glaucum), African Yam Bean (Sphenostylis stenocarpa), and Jackfruit (Artocarpus heterophyllus) Flour Blends: A Comparative Study

Abstract: The progress towards exploring the potentials of underutilized indigenous food sources via product development to curb food wastage and agro-food extinction is a way of attaining food nutrition and security within a region. In this context, a comparative study involving some functional properties of complementary food from some underutilized foods (millet, African yam bean, and jackfruit) was carried out. Briefly, millet, African yam bean, and jackfruit were subjected to series of processing treatments such as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 34 publications
0
0
0
Order By: Relevance
“…The lower the pasting temperature, the better from energy conservation principle as it relates directly to cost of energy involved in production process. This trend of results in this present study is similar to what was reported by Alimi et al [6] and Eke et al [34].…”
Section: Pasting Properties Of the Composite Flourssupporting
confidence: 93%
See 1 more Smart Citation
“…The lower the pasting temperature, the better from energy conservation principle as it relates directly to cost of energy involved in production process. This trend of results in this present study is similar to what was reported by Alimi et al [6] and Eke et al [34].…”
Section: Pasting Properties Of the Composite Flourssupporting
confidence: 93%
“…The higher the breakdown viscosity, the lower the ability of starch in the flour samples to withstand heating and shear stress [33]. Relatively, increased quantity of Bambara groundnut flour in the composite flours tends to reduce the breakdown viscosity of the flour blends and this trend has been reported by previous studies on composite flours [34].…”
Section: Pasting Properties Of the Composite Flourssupporting
confidence: 53%
“…Flours with low bulk density are typically utilised in infant and weaning food preparations, while those with high bulk density are commonly employed as thickeners and stabilisers in processed foods (David et al ., 2015). Considering the bulk density value of 0.555 g/cm 3 , the micronized DSPC appears to be suitable for complementary food preparations (Eke‐Ejiofor et al ., 2021).…”
Section: Resultsmentioning
confidence: 99%